Analisis Faktor-Faktor yang Mempengaruhi Perilaku Impulsive Buying Generasi Muda: Studi Empiris pada Penggemar Merchandise K-Pop - Lestari, Resti Ayu; Setyaning, Alldila Nadhira Ayu (Universitas Negeri Padang, 2025)
This study aims to analyze the factors influencing impulsive buying behavior among young consumers, specifically fans of K-Pop merchandise. Impulsive buying behavior refers to unplanned and spontaneous purchases, often triggered by emotional and social factors. This research adopts a quantitative approach through a survey method involving 202 respondents aged 18–29 who have engaged in impulsive purchases of K-Pop merchandise. The sampling technique used is convenience sampling. The variables examined include low self-control, positive attitude toward targeted advertising, and social network impulsiveness. Hypothesis testing was conducted using Structural Equation Modeling with the Partial Least Squares (SEM-PLS) method. The results show that low self-control significantly influences impulsive buying behavior, both directly and indirectly, through its effects on targeted advertising attitudes and social network impulsiveness. These findings contribute to a deeper understanding of the psychological and social mechanisms behind impulsive consumer behavior in the context of digital popular culture fandoms.